Risk Analysis of Bridge Team Management on Navigational Safety in the Mahakam River Fairway - Yunus Hans Cristian Sihotang; Dion Lebang; Sunarlia Limbong (Darul Yasin Al Sys, 2026)
Although navigational risk management has received considerable attention in maritime safety research, few studies have quantified collision and grounding risks in Indonesia’s narrow river fairways using long-term incident records. This study analyzed the risk levels of collision and grounding incidents involving KM. Tonasa Line XIX in the Mahakam River Fairway and evaluated compliance with Bridge Resource Management (BRM) practices in maintaining navigational safety. A descriptive qualitative approach was employed, drawing on BRM theory, Human Factors Theory, Situational Awareness Theory, the International Regulations for Preventing Collisions at Sea 1972, and the International Safety Management Code. Data were collected through direct observation during sea practice, in-depth interviews with the Master and three Deck Officers, and a literature review. Risk quantification was conducted using the Formal Safety Assessment framework established in IMO MSC/Circ.1023 and based on 25 verified incidents recorded in the fairway between 2021 and 2026. The findings identified human error—including fatigue, miscommunication, and inappropriate decision-making—and environmental conditions, such as channel siltation, strong currents, and high traffic density, as the dominant risk drivers. Based on the formula Risk Score = Likelihood × Consequence, collision incidents, comprising at least 17 cases, and grounding incidents, comprising at least eight cases, each received a score of 9 and were classified as high risk. The study concludes that BRM procedures are available on board but are not consistently implemented, particularly in relation to situational awareness, assertive communication, and fatigue management. These findings extend the literature on incident-history-based Formal Safety Assessment in confined waterways and provide practical implications for shipping companies, bridge officers, and waterway authorities seeking to strengthen navigational safety in the Mahakam River corridor. The study also provides a basis for future comparative research involving multiple vessels and river fairways.